Thermodynamic quantities of solvation and dilution for some acetanilide derivatives in octanol and water mutually saturated - Baena, Yolima; Barbosa, Helber; Martínez, Fleming (Eclética Química, 2008)
Based on published thermodynamic quantities for solution, partitioning and sublimation of acetanilide (ACN), acetaminophen (ACP) and Phenacetin (PNC), the thermodynamic quantities for drugs solvation in octanol-saturated water (W(ROH)) and water-saturated octanol (ROH(W)) as well as the drugs dilution in ROH(W) were calculated. The Gibbs energies of solvation were favourable in all cases. The respective enthalpies and entropies were negative indicating an enthalpy-driving for the solvation process in all cases. On the other hand, the Gibbs energies of dilution were favourable for ACP and PNC but unfavourable for ACN, whereas the respective enthalpies and entropies were negative for ACP and PNC but positive for ACN indicating enthalpy-driving for the dilution process in the case of the former drugs and entropy-driving for the latter. From the obtained values for the transfer processes, an interpretation based on solute-solvent interactions was developed.